1-D oriented cross-linking hierarchical porous carbon fibers as a sulfur immobilizer for high performance lithium–sulfur batteries. Issue 16 (4th April 2016) - Yang, Xiaofei; Yu, Ying; Yan, Na; Zhang, Hongzhang; Li, Xianfeng; Zhang, Huamin
Abstract : 1D oriented ordered cross-linking hierarchical porous carbon fibers were fabricated successfully. The prepared cross-linking hierarchical porous carbon fibers (CHPCF) as the sulfur immobilizer demonstrated excellent cycling stability and high C-rate performance in Li–S batteries. Abstract : One-dimensional (1D) oriented cross-linking hierarchical porous carbon fibers (CHPCF) were designed and proposed as the sulfur immobilizer for application in lithium–sulfur (Li–S) batteries. The CHPCFs exhibit a large length/diameter ( L / D ) ratio, a cross-linked structure and a reasonable hierarchical porous distribution, which provides "green channels" for both e − and Li + transport. Besides, the CHPCFs possess large micro-porous surfaces to confine the polysulfide (PS) diffusion. As a result, the S/CHPCF cathodes simultaneously achieve excellent C-rate performance and cycling stability of 535 mA h g −1 at 15C (1C = 1672 mA g −1 ), and 0.076% capacity attenuation per cycle at 5C during 500 cycles. The structure–performance relationship of the carbon materials and Li–S batteries was studied in detail. This research work sheds light on material design for Li–S batteries with excellent C-rate performance.